Review of the National Examination Policy in the Learning Evaluation Paradigm and its Implications for Madrasah Students - Aries Musnandar; Salim Salim (Yayasan Adra Karima Hubbi, 2024)
The National Examination (UN) policy, which has been implemented in Indonesia for a long time, has a number of weaknesses in terms of educational science. The UN is not